Self-consistent modelling of cyclic loading and relaxation in austenitic 316H stainless steel - Petkov, M; Hu, J; Cocks, A (Taylor and Francis, 2018)
In the present study the Hu-Cocks micromechanical model [1,2] for dislocation-obstacle interactions, implemented in a crystal plasticity self-consistent model, is employed to simulate thermo-mechanical histories typical for AGR nuclear plants in order to assess the implications of creep-fatigue interactions in 316H stainless steel. Their physical model is enhanced by including the effect of dynamic recovery, which introduces a new material parameter – the annihilated segment length ΔLr. The full model contains five independent material parameters; other parameters are prescribed by the fundamental physics of inelastic deformation processes. Having calibrated the model, we explore its ability to predict material response under complex loading histories to provide insight into the physical phenomena controlling cyclic-creep interactions. Introduction of strain dwells during cyclic loading results in an increase of the extent of relaxation with an increasing number of cycles, but histories with dwells at different strain levels indicate that relaxation is strongly dependent on initial stress and level of constant strain. Predictions of history-dependent relaxation demonstrate that the least stress relaxation results after creep into the secondary regime and the largest stress drop results during hold-dwells after monotonic elastic-plastic loading, with the cyclic-dwell history behaviour laying in between these two. Both prior cycling and the generated residual stress field are found to affect the primary creep regime under hold-stress dwells. These results are consistent with experimental observations; this demonstrates that deformation response is dependent on both the evolution of microstructural state and redistribution of stress between the grains of the polycrystalline aggregate.